2012
DOI: 10.1007/s00540-012-1353-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gastric distension in patients with acute appendicitis: a retrospective cohort study

Abstract: Younger appendicitis patients with acute abdominal pain for 1 or more days should be treated as patients with high risk for GD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The incidence was higher in younger patients and those with a longer duration of abdominal pain [5]. A subsequent ultrasound study conducted in a mixed adult-paediatric population with acute appendicitis found that 62% of patients had an empty stomach before surgery, for which the probability increased with the duration of fasting [6].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The incidence was higher in younger patients and those with a longer duration of abdominal pain [5]. A subsequent ultrasound study conducted in a mixed adult-paediatric population with acute appendicitis found that 62% of patients had an empty stomach before surgery, for which the probability increased with the duration of fasting [6].…”
Section: Discussionmentioning
confidence: 97%
“…The incidence was higher in younger patients and those with a longer duration of abdominal pain [5]. A subsequent ultrasound study conducted in a mixed adult–paediatric population with acute appendicitis found that 62% of patients had an empty stomach before surgery, for which the probability increased with the duration of fasting [6]. Finally, in a recent study comparing pre‐operative gastric contents of adults with uncomplicated acute appendicitis with those of controls (adults scheduled for elective non‐abdominal surgery), gastric ultrasound showed that only 18% of patients had at‐risk gastric contents after 6 h of fasting, which was not significantly different from controls [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation